Pengaruh Struktur Keuangan Terhadap Manajemen Laba Perusahaan Manufaktur Tahun 2019-2023 - Annisa Rahmadiani Imron; Azizah Inas Pratiwi; Syafira Enggar Khoirul Nisa; Muhammad Fauzi Khoirul; Safanella Fildza Fatihah; Reza Asti Choirunisa (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
Earnings management is a practice frequently carried out by companies to influence financial statements according to certain goals, such as enhancing financial image or avoiding tax regulations. The financial structure of a company, including liquidity, leverage, capital intensity, and firm size, may play a role in influencing such earnings management practices. This study aims to analyze the effect of financial structure on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2019–2023. The data used are secondary data obtained from financial reports of companies listed on the IDX. The study employs purposive sampling, selecting 55 companies from a total of 171 companies listed, meeting specific criteria, and 260 data points were selected for analysis over the five-year study period. The results of the study indicate that liquidity, leverage, and firm size do not have an impact on earnings management, while capital intensity has a negative effect on earnings management in manufacturing companies.